Concept of sustainable development in the system of international environmental law - Kupchenia, Lidia (ScienceRise: Juridical Science, 2022)
The essence of the concept of sustainable development and its significance for environmental protection by means of international law are analyzed. For this purpose, foreign and domestic scientific literature is researched, as well as legal documents, which formulate the goals of sustainable development. It is proved, that the concept of sustainable development should be considered in the system of international law in general, and in International Environmental Law in particular. This approach is due to the consequences of the global economic crisis, COVID-19 and Russia’s military aggression against Ukraine. Since the maintenance of international order depends on sustainable development, the main goals of sustainable development are listed, the implementation of which guarantees stability in the world, which should be the basis of international law. Implementing the goals of sustainable development, restoring balance in nature and international relations are expected to be provided by individuals, so understanding the essence of global social processes is extremely important, which indicates the relevance of the study. The development trends of such an international organization as the World Trade Organization, which intensified its activities after the Russian invasion of the sovereign territory of Ukraine on February 24, 2022, are analyzed separately, in particular on issues, such as food security. At the same time, the necessity of using legal, in particular judicial, methods of resolving disputes between WTO members along with diplomatic ones was argued. In general, this work is based on the statement about the importance of implementing the concept of sustainable development to minimize risks, in particular in the field of nuclear safety. It is the priority of stable development of the states that ensure the operation of nuclear power plants that will guarantee global environmental security, which determines the essence of international environmental law, the content and direction of the legal norms that shape it